Microbiota and Mitochondrial Sex-Dependent Imbalance in Fibromyalgia: A Pilot Descriptive Study - Jorge A. Ramírez-Tejero; Elena Durán-González; Antonio Martínez-Lara; Laura Lucena del Amo; Isabel Sepúlveda; Andrés Huancas-Díaz; Marco Carvajal; David Cotán (MDPI AG, 2023)
Fibromyalgia is a widespread chronic condition characterized by pain and fatigue. Among the long list of physiological disturbances linked to this syndrome, mitochondrial imbalance and oxidative stress stand out. Recently, the crosstalk between mitochondria and intestinal microbiota has caught the attention of biomedical researchers, who have found connections between this axis and several inflammatory and pain-related conditions. Hence, this pilot descriptive study focused on characterizing the mitochondrial mass/mitophagy ratio and total antioxidant capacity in PBMCs, as well as some microbiota components in feces, from a Peruvian cohort of 19 females and 7 males with FM. Through Western blotting, electrochemical oxidation, ELISA, and real-time qPCR, we determined VDAC1 and MAP1LC3B protein levels; total antioxidant capacity; secretory immunoglobulin A (sIgA) levels; and Firmicutes/Bacteroidetes, Bacteroides/Prevotella, and Roseburia/Eubacterium ratios; as well as Ruminococcus spp., Pseudomonas spp., and Akkermansia muciniphila levels, respectively. We found statistically significant differences in Ruminococcus spp. and Pseudomonas spp. levels between females and males, as well as a marked polarization in mitochondrial mass in both groups. Taken together, our results point to a mitochondrial imbalance in FM patients, as well as a sex-dependent difference in intestinal microbiota composition.